Satisfaction with Past Financial Performance, Risk Taking, and Future Performance Expectations in the Family Business. (29th December 2013) - Mahto, Raj V.; Khanin, Dmitry; Henry, Colette; Foss, Lene; Fayolle, Alain; Walker, Elizabeth; Duffy, Susan
<x xml:space="preserve">Abstract</x> Prior research has shown that past financial performance and risk‐taking proclivity influence firms' goal setting and future performance expectations. In this study, we analyze how such factors manifest themselves in the context of the family business. Drawing from the behavioral theory of the firm, we argue that owners–managers of family firms satisfied with their past financial performance will correspondingly upgrade their future performance expectations. Based on strategic reference points theory, we also propose that satisfaction with past performance in family firms will be negatively associated with risk taking. Finally, we conjecture that family firms may exhibit heterogeneity in their risk orientation so that greater risk taking will be positively associated with family firms' future performance expectations. The results of structural equation modeling analysis of two combined surveys of family firms supported the hypotheses.